2010
DOI: 10.1186/1479-5876-8-2
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative real time PCR method to analyze T cell receptor Vβ subgroup expansion by staphylococcal superantigens

Abstract: BackgroundStaphylococcal enterotoxins (SEs), SE-like (SEl) toxins, and toxic shock syndrome toxin-1 (TSST-1), produced by Staphylococcus aureus, belong to the subgroup of microbial superantigens (SAgs). SAgs induce clonal proliferation of T cells bearing specific variable regions of the T cell receptor β chain (Vβ). Quantitative real time PCR (qRT-PCR) has become widely accepted for rapid and reproducible mRNA quantification. Although the quantification of Vβ subgroups using qRT-PCR has been reported, qRT-PCR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 33 publications
3
39
0
Order By: Relevance
“…9C). These results were identical to those previously observed with CD4+ T cells (29). Flow cytometry results further confirmed the quantitative real time PCR results showing an increase of Vβ 14 after stimulation with SEC1 (Fig.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…9C). These results were identical to those previously observed with CD4+ T cells (29). Flow cytometry results further confirmed the quantitative real time PCR results showing an increase of Vβ 14 after stimulation with SEC1 (Fig.…”
Section: Resultssupporting
confidence: 92%
“…Selective expansion of TCR Vβ was assessed by quantitative real-time PCR using an ABI Prism 7500 real-time PCR system (Applied Biosystems, Foster City, CA) as described previously (29). …”
Section: Methodsmentioning
confidence: 99%
“…15 However, previous investigations did not detect any Vb11 expansion in response to a number of staphylococcal SAgs including those tested in our study. 52,53 We found that human iNKT cells upregulate their CD69 expression shortly after exposure to SEB, which provides the initial report that human iNKT cells are responsive to bacterial SAgs. These discrepancies may be because of different readouts used (Vb11 expansion among PBMCs in previous studies as opposed to early CD69 expression on iNKT cells in our study).…”
Section: Human Inkt Cells Are Activated By Bacterial Sagsmentioning
confidence: 61%
“…28 The analysis of TRBV usage in an individual can help in the evaluation of the immune response in a variety of conditions over the course of the disease. 29 Many studies have determined that the usage frequency of antigen-specific TRBV families in subjects with either virus infection or cancer can be different. 30,31 In the current study, the increased expression of several TRBV families was detected in CD4 1 and CD8 1 T-cell populations, which is consistent with observations that the T-cell immune response to HBV antigens involves multiple TRBV families.…”
Section: In Cd4mentioning
confidence: 99%